2018
DOI: 10.1093/annonc/mdy417
|View full text |Cite
|
Sign up to set email alerts
|

Repeated mutKRAS ctDNA measurements represent a novel and promising tool for early response prediction and therapy monitoring in advanced pancreatic cancer

Abstract: Background: The presence of mutated KRAS ( mut KRAS ctDNA) in plasma samples has been consistently shown to be a negative prognostic indicator in pancreatic cancer (PC). Only small pilot studies have evaluated the value of serial mut KRAS ctDNAmeasurements in PC. Patients and methods:The aim of the present study was to explore the potential of repeated mut KRAS ctDNA measurements for response prediction and therapy monitoring in advanced PC patients. We used the BEAMing technology to determine levels of mut KR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 20 publications
10
127
0
3
Order By: Relevance
“…Not unexpectedly, characterized alterations in ctDNA were more frequent in patients with advanced PDAC than in those with surgically resectable disease (median, 2 versus 0.5, P = 0.04); median of maximum %ctDNA (0.4% versus 0%, P = 0.02) and median of total %ctDNA (0.6% versus 0%, P = 0.007) were also higher ( Table 1). These findings are consistent with a previous report showing that ctDNA was more easily detectable in patients with metastatic cancer than those with localized diseases [43,44]. Higher tumor load presumably increases ctDNA shedding to blood.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Not unexpectedly, characterized alterations in ctDNA were more frequent in patients with advanced PDAC than in those with surgically resectable disease (median, 2 versus 0.5, P = 0.04); median of maximum %ctDNA (0.4% versus 0%, P = 0.02) and median of total %ctDNA (0.6% versus 0%, P = 0.007) were also higher ( Table 1). These findings are consistent with a previous report showing that ctDNA was more easily detectable in patients with metastatic cancer than those with localized diseases [43,44]. Higher tumor load presumably increases ctDNA shedding to blood.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have found similar results [45][46][47]. Discordant cases that were positive in tissue and negative in ctDNA have been previously explained by low tumor load in surgically resectable cases [43,44]. In addition, detection of ctDNA can be affected by systemic treatment prior to blood draw [48,49].…”
Section: Discussionsupporting
confidence: 53%
“…This result indicates that ctDNA FGFR2 mutations could be used to identify resistance of the FGFR inhibitor BGJ398 [124]. Studies examining circulating free DNA responses to the drug have also been conducted in ovarian carcinoma [125], colorectal cancer [65,126,127] and pancreatic cancer [128]. Moreover, regorafenib seems to be consistently associated with a clinical benefit in patients based on mutational status and protein biomarker concentration, indicating that the detection of circulating DNA could be a viable approach for noninvasive analysis of the tumor genotype in real time [129].…”
Section: Surgerymentioning
confidence: 94%
“…Correspondingly, PC patients with KRAS mutant ctDNA were more likely to relapse after curative surgery than those without KRAS mutant ctDNA with deseasefree survival of 6.1 versus 16.1 months and overall survival of 13.6 versus 27.6 months (p < 0.001) (Groot et al 2019;Hadano et al 2016;Sausen et al 2015). Serial plasma testing of KRAS mutant ctDNA in advanced PC patients receiving chemotherapy allowed the monitoring of rapid changes of KRAS mutant ctDNA levels superior to CA19-9 and CEA kinetics (Kruger et al 2018). Targeting KRAS pathway is a promising effort to make therapeutic progress in PC (Krantz and O'Reilly 2018).…”
Section: Genomic Alterations Of Ctdna In Pcmentioning
confidence: 99%
“…Therefore, KRAS mutant ctDNA represents a promising biomarker and therapeutic target of PC. Using ddPCR and targeted NGS, different KRAS mutations were detected in up to 80% of PC serum and plasma samples and were associated with decreased survival (Adamo et al 2017;Ako et al 2017;Chen et al 2010;Cohen et al 2017;Dabritz et al 2009;Del Re et al 2017;Dianxu et al 2002;Earl et al 2015;Hadano et al 2016;Jiao et al 2007;Kim et al 2018;Kinugasa et al 2015;Kruger et al 2018;Lin et al 2018;Maire et al 2002;Marchese et al 2006;Nakano et al 2018;Park et al 2018;Patel et al 2019;Perets et al 2018;Pratt et al 2019;Riviere et al 2018;Sausen et al 2015;Semrad et al 2015;Sugimori et al 2020;Takai et al 2015;Tjensvoll et al 2016;Uemura et al 2004;Van Laethem et al 2017;Watanabe et al 2019;Wu et al 2014). Chen et al published a KRAS mutant ctDNA detection rate of 93.7% which correlates with time to progression and overall survival of 189 patients with unresectable PC (Chen et al 2017).…”
Section: Genomic Alterations Of Ctdna In Pcmentioning
confidence: 99%